Archaeological research on 17th-18th-century Baturyn in 2018 - Mezentsev, V.I.; Sytyi, Yu.M.; Kovalenko, Yu.O. (Сіверщина в історії України, 2019)
This article demonstrates Western influences on the fortifications and
layout of Hetman I. Mazepa’s estate near Baturyn. It also examines the
excavated remnants of residences and service structures constructed by
I. Mazepa, Chancellor General P. Orlyk, and Hetman K. Rozumovsky, as
well as the ceramic stove tiles executed in Ukrainian and Dutch baroque
styles, and other 17th-18th-century archaeological finds in the town in
2018. Computer reconstructions of the fragmented tiles with the coats
of arms of P. Orlyk and I. Mazepa are published and discussed. Стаття демонструє західні впливи на фортифікацію та планування маєтку гетьмана І. Мазепи під Батурином. Розглядаються розкопані рештки житлових і службових споруд І. Мазепи, генерального писаря П. Орлика й гетьмана К. Розумовського, керамічні
пічні кахлі за стилями українського і голландського бароко та інші
археологічні знахідки XVII–XVIII ст. у місті в 2018 р. Публікуються
і аналізуються комп’ютерні реконструкції фрагментованих кахлів
з гербами П. Орлика та І. Мазепи. Статья демонстрирует западные влияния на фортификацию и
планировку усадьбы гетмана И. Мазепы под Батурином. Рассматриваются раскопанные остатки жилых и служебных построек И. Мазепы, генерального писаря Ф. Орлика и гетмана К. Разумовского, керамические печные изразцы в стилях украинского и голландского
барокко и другие археологические находки XVII–XVIII вв. в городе в
2018 г. Публикуются и анализируются компьютерные реконструкции фрагментированных изразцов с гербами Ф. Орлика и И. Мазепы.